2001
DOI: 10.1046/j.1532-5415.2001.49041.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in Older Adults: Prevention and Treatment

Abstract: The release of guidelines in 1998 by the American Geriatrics Society on "The Management of Chronic Pain in Older Persons" was a breakthrough in helping to manage pain in this population. Already advances have fostered a need to update recommendations. This article focuses on the treatment strategies available for seniors that are likely to help to fulfill the obligation to relieve pain and suffering in patients. A review was done of the literature using Medline and other search techniques. New pain scales have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
115
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 80 publications
(116 reference statements)
2
115
1
6
Order By: Relevance
“…Similar findings in older people's decision making about the management of musculoskeletal pain showed that they focused on the negative dimensions of medication and preferred to use a combination of strategies to relieve the pain (Ross et al, 2001). The drug distribution is usually different in older patients because of blood flow to organs, protein binding and body composition that occurs with ageing (Gloth, 2001). This could explain the experiences of side effects described in this study, since the majority of the respondents were over 75 years old.…”
Section: Discussion Of the Findingsmentioning
confidence: 80%
“…Similar findings in older people's decision making about the management of musculoskeletal pain showed that they focused on the negative dimensions of medication and preferred to use a combination of strategies to relieve the pain (Ross et al, 2001). The drug distribution is usually different in older patients because of blood flow to organs, protein binding and body composition that occurs with ageing (Gloth, 2001). This could explain the experiences of side effects described in this study, since the majority of the respondents were over 75 years old.…”
Section: Discussion Of the Findingsmentioning
confidence: 80%
“…5 Transcutaneous electrical nerve stimulation (TENS), acupuncture, relaxation techniques and massage may all be of benefit. Appropriate Prescribing in older people review and inter vention by both physiotherapy and occupational therapy may improve pain through rehabilitation and functional aids.…”
Section: Nonpharmacological Pain Interventionsmentioning
confidence: 99%
“…Brown et al report higher percentage and state that more than 90% of the elderly living in the community experienced pain within the past month [6]. Given the prevalence of chronic pain, its impact on health, and its costs, which approach $100 billion annually, chronic pain represents a major public health issue [20].While the existence of acute pain remains approximately the same across the adult life span, there is an age-related increase in the prevalence of chronic pain at least until the seventh decade of life [13,15]. Approximately 57% of older adults report experiencing pain for 1 or more years compared with less than 45% of younger people.…”
mentioning
confidence: 99%
“…
Pain in Perspective 94percent of community dwelling adults aged 60 years or above have been found to experience pain and this number increases to 45-80% in the nursing home population with analgesics being used in 40% to 50% of residents [1,[13][14][15][16][17][18][19]. Brown et al report higher percentage and state that more than 90% of the elderly living in the community experienced pain within the past month [6].
…”
mentioning
confidence: 99%
See 1 more Smart Citation